Changes in dietary habit and physical activity among the diabetic patients of Bangladesh during COVID-19: A cross-sectional study. - Ishrat Jahan; A B M Nahid Hasan; Azaz Bin Sharif; Sharmin Akter (Public Library of Science (PLoS), 2023)
In an effort to avert further Covid-19 transmission, the Bangladesh government took several initiatives which disrupted the routine food intake and exercise of diabetic patients. This study sought to examine the difference in dietary and exercise habits of diabetic patients between their pre-pandemic status and during COVID-19 which may be attributed to the observed poor health outcomes during the study period. This was a cross-sectional study that enrolled 604 diabetic patients using a convenience sampling technique who were attending outpatient clinics of the three selected hospitals in Bangladesh. A validated semi-structured questionnaire was used to collect information regarding eating habit and physical activity of the respondents pre- and during COVID-19 pandemic via direct interview. McNemar-Bowker test was used to assess the changes in dietary and physical activity behaviors. The current study reveals that 93.9% of the respondents were type-2 diabetic patients. During the pandemic, there was a decrease in the consumption of rice, bread, meat, fish, eggs, and dessert, while the consumption of cereals, milk, and potato/starchy vegetables increased. There was also a decrease in the frequency of drinking tea or coffee, while the consumption of soft drinks remained relatively stable. The level and duration of physical activity significantly decreased among the respondents during the pandemic. This study explored the changes in dietary habits and physical activity among the study population which not only disrupt the metabolic control of the diabetic patients but also pose a significant threat to their overall health. Therefore, it is critical to prioritize measures that support diabetic patients to maintain healthy dietary habit and to engage in regular physical activity during unprecedented times such as COVID-19 pandemic.